2016
DOI: 10.1177/1470320316647240
|View full text |Cite
|
Sign up to set email alerts
|

Plasma oxidative stress level of IgA nephropathy in children and the effect of early intervention with angiotensin-converting enzyme inhibitors

Abstract: Aim:The purpose of this study was to investigate the change of the plasma oxidative stress level in children with IgA nephropathy (IgAN) and analyze its relativity to the clinical and pathological classification. To discuss the early effects of angiotensin-converting enzyme inhibitors (ACEIs) on the plasma oxidative stress level in children with IgA nephropathy.Methods:Thirty-eight children with IgAN were divided into groups according to their clinical features, pathologic grades, and treatments. Twenty health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…By using the MDA analysis and/or the TBA test, also making a sample measurements interpretation, we may determine the OS within an organism (Trevisan et al 2001 ). For instance, MDA measurements were carried out in a study that included a group of 38 children diagnosed with IgA nephropathy in order to assess whether the serum OS biomarkers levels measurements can be potentially used as a non-invasive diagnostic method in this disease (Pei et al 2016 ). It was reported that the increased plasma level of advanced oxidation protein products and MDA were detected, and the SOD serum levels were decreased (Pei et al 2016 ).…”
Section: Biomarkers Of Osmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the MDA analysis and/or the TBA test, also making a sample measurements interpretation, we may determine the OS within an organism (Trevisan et al 2001 ). For instance, MDA measurements were carried out in a study that included a group of 38 children diagnosed with IgA nephropathy in order to assess whether the serum OS biomarkers levels measurements can be potentially used as a non-invasive diagnostic method in this disease (Pei et al 2016 ). It was reported that the increased plasma level of advanced oxidation protein products and MDA were detected, and the SOD serum levels were decreased (Pei et al 2016 ).…”
Section: Biomarkers Of Osmentioning
confidence: 99%
“…For instance, MDA measurements were carried out in a study that included a group of 38 children diagnosed with IgA nephropathy in order to assess whether the serum OS biomarkers levels measurements can be potentially used as a non-invasive diagnostic method in this disease (Pei et al 2016 ). It was reported that the increased plasma level of advanced oxidation protein products and MDA were detected, and the SOD serum levels were decreased (Pei et al 2016 ). Interestingly, it has been reported that serum MDA can be downregulated by a recently synthesized caffeic acid derivative: N -propyl caffeamide (Cheng et al 2017 ), which belongs to a class of potent candidates for anti-inflammatory and cardioprotective drugs.…”
Section: Biomarkers Of Osmentioning
confidence: 99%
“…Previous studies have shown that oxidative stress plays an important role in the pathophysiology of IgAN [ 13 17 ]. Advanced oxidation protein products (AOPPs), markers of oxidative stress, were higher in the serum of patients with IgAN than those of healthy controls, and levels of AOPPs were correlated with the rate of decline in renal function [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…PUFAs play protective effects on renal function ( Taccone-Gallucci et al, 2006 ; Lauretani et al, 2008 ; Eide et al, 2016 ; Malhotra et al, 2016 ) and are highly susceptible to oxidative damage ( Yang et al, 2016 ). Intrarenal reactive oxygen species (ROS) that increase oxidative stress play a pivotal role in the development of IgAN ( Pei et al, 2016 ). Enhanced oxidative stress levels in the plasma and kidneys in IgAN patients could be the cause of the decreased plasma level of PUFAs ( Kobori et al, 2007 ; Pei et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intrarenal reactive oxygen species (ROS) that increase oxidative stress play a pivotal role in the development of IgAN ( Pei et al, 2016 ). Enhanced oxidative stress levels in the plasma and kidneys in IgAN patients could be the cause of the decreased plasma level of PUFAs ( Kobori et al, 2007 ; Pei et al, 2016 ). Recent studies suggested that increasing intake of PUFAs, such as DHA and eicosapentaenoic acid (EPA), significantly decreased plasma lipid hydroperoxide, a consequence of ROS overproduction ( Hassler et al, 2014 ) and is effective in the treatment of human IgAN ( Lee et al., 2013 ; Hirahashi, 2017 ).…”
Section: Discussionmentioning
confidence: 99%